Investigation of the Antibacterial and Antibiofilm Activity of Selenium Nanoparticles against Vibrio cholerae as a Potent Therapeutics - Sareh Bagheri-Josheghani; Bita Bakhshi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Vibrio cholerae is a major cause of severe diarrhea, which is ecologically flexible, and remains as a major cause of death, especially in developing countries. Consecutive emergence of antibiotic-resistant strains is considered to be as one of the major concerns of the World Health Organization (WHO). Nanoparticles as a new nonantibiotic therapeutic strategy have been widely used in recent years to treat bacterial infections. The present study aimed to investigate the antibacterial and antibiofilm effect of selenium nanoparticles (SeNPs) in vitro against V. cholerae O1 ATCC 14035 strain. SeNPs were prepared and characterized using ultraviolet-visible (UV-Vis) spectroscopy, DLS (dynamic light scattering), zeta potential measurement, and Fourier transform infrared (FTIR) analysis. The concentration of SeNPs was calculated by ICP (inductively coupled plasma) method. Also, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was employed to assess the cytotoxic effect of SeNPs on Caco-2 cells. Antibacterial and antibiofilm activity of SeNPs was determined by broth microdilution and crystal violet assays, respectively. The average particle size of SeNPs was 71.1 nm with zeta potential −32.2 mV. The SEM images supported the uniform spherical morphology of the prepared nanoparticles. The antibiofilm effect of SeNPs was evident at concentrations of 50–200 μg/mL. This study results provided evidence that SeNPs are safe as an antibacterial and antibiofilm agent against V. cholerae O1 ATCC 14035 strain.